Contents of mineral elements in grain of different rice varieties (Eurasian Journal of Ecology, 2018)
It was studied the content of mineral elements such as magnesium (Mg), iron (Fe), zinc (Zn), manganese (Mn), copper (Cu),as well as cadmium (Cd) in grains of different rice varieties.The objects of research were different varieties of rice (Oryza sativa L.).Bakanassky RM-2000-183 – maturing rice variety, completely adapted tothe conditions in the rice-growing Akdalinski irrigation array (Balkhash district of Almaty region, “Birlik” LLP); Marzhan – middle-grade (originatorKazakh Research Institute of Rice, Kyzylorda, were zoned in 1987 for theKyzylorda region; Violetta – glutinous variety of rice (Rice Research Institute, 2001; Krasnodar, Russia), and Anayt, Fisht – amylose rice varieties ofRussian breeding; Barakat – Chinese variety, Chapsari – Korean rice variety with a high content of gluten. The magnesium content was highest invarieties Anayt, Marzhan and Madina. The lowest magnesium content wasfound in the variety Bakanas. The remaining varieties occupied an intermediate position on magnesium content. Rice varieties on the magnesiumcontent are located in the following order (µg/g): Anayt (1746.0)>Marzhan(1632.0)>Madina (1622.0)>Violetta (1421.0)>Fischt (1344.0)>Barakat(1259.0)>Chapsari (1213.0)>Baқanas (1205.0). Manganese contained inthe largest amount in the grain of Chapsarivarieties, the least amount ofmanganese found in grains of Fisht and Bakanasvarieties. According tothe content of manganese in grain varieties were located as follows (g / g):Chapsari (33.9)>Barakat (25.0)>Madina (21.5)>Marjane (20.5)>Anahit (19.8)>Violetta (19.4)>Fischt (16.45)>Baқanas (14.8). The highestiron content found in grains of Bakanas variety. Marzhan, Barakat, Violettavarieties are distinguished by low iron content (10,45-11,5 µg/g). The remaining varieties occupy an intermediate position: Anay variety have thehighest concentration of magnesium, in Chapsari variety was detected thehighest content of manganese in comparison with other studied varieties.Bakanas cultivar contained the highest amount of iron. Fischt and Barakatvarieties have a relatively low number of investigated elements.Key words: rice, cadmium, growth, stability, variety